RENCANA ANGGARAN BIAYA UNTUK SUMUR RESAPAN MASJID BESAR KOTA BANJARBARU - Aulia Isramaulana (Universitas Lambung Mangkurat, 2014)
Banjarbaru is one of the cities in South Borneo, which has developed very rapidly in line with the growth of population and the physical building. This has implications for the decreasing availability of water catchment areas. Therefore it is necessary to built recharge wells to avoid a puddle of water on the surface. This study aimed to quantify the discharge of rain and water for ablution, plan dimensions and the number of recharge wells and budget plans for a large mosque in Banjarbaru.The infiltration wells design using Sunjoto formula. To determine the coefficient of permeability of the soil, tested in the field by using a double ring infiltrometer and testing in the laboratory by using Constant Head Test. This Tests on three major mosques in Banjarbaru , the first is Al-Munawaroh Mosque, Jami Hidayatul Muhajirin Mosque, and Al-Baythar Mosque.The result is Al-Munawaroh Mosque designed infiltration wells depth of 5 m at a cost of one unit of infiltration wells Rp. 4,842,900.00, whereas for Hidayatul Muhajirin Mosque Al-Baythar Mosque designed depth of 3 m at a cost of one unit of infiltration wells Rp. 3,406,700.00. Keywords: infiltration wells, budget plan, Banjarbaru Mosque